Direct Nitrous Oxide Emission from the Aquacultured Pacific White Shrimp (Litopenaeus vannamei) - Heisterkamp, Ines M. (Appl Environ Microbiol, 2016)
The Pacific white shrimp (Litopenaeus vannamei) is widely used in aquaculture, where it is reared at high stocking densities, temperatures, and nutrient concentrations. Here we report that adult L. vannamei shrimp emit the greenhouse gas nitrous oxide (N(2)O) at an average rate of 4.3 nmol N(2)O/individual × h, which is 1 to 2 orders of magnitude higher than previously measured N(2)O emission rates for free-living aquatic invertebrates. Dissection, incubation, and inhibitor experiments with specimens from a shrimp farm in Germany indicated that N(2)O is mainly produced in the animal's gut by microbial denitrification. Microsensor measurements demonstrated that the gut interior is anoxic and nearly neutral and thus is favorable for denitrification by ingested bacteria. Dinitrogen (N(2)) and N(2)O accounted for 64% and 36%, respectively, of the nitrogen gas flux from the gut, suggesting that the gut passage is too fast for complete denitrification to be fully established. Indeed, shifting the rearing water bacterial community, a diet component of shrimp, from oxic to anoxic conditions induced N(2)O accumulation that outlasted the gut passage time. Shrimp-associated N(2)O production was estimated to account for 6.5% of total N(2)O production in the shrimp farm studied here and to contribute to the very high N(2)O supersaturation measured in the rearing tanks (2,099%). Microbial N(2)O production directly associated with aquacultured animals should be implemented into life cycle assessments of seafood production. IMPORTANCE The most widely used shrimp species in global aquaculture, Litopenaeus vannamei, is shown to emit the potent greenhouse gas nitrous oxide (N(2)O) at a particularly high rate. Detailed experiments reveal that N(2)O is produced in the oxygen-depleted gut of the animal by bacteria that are part of the shrimp diet. Upon ingestion, these bacteria experience a shift from oxic to anoxic conditions and therefore switch their metabolism to the anaerobic denitrification process, which produces N(2)O as an intermediate and dinitrogen (N(2)) gas as an end product. The N(2)O/N(2) production ratio is unusually high in the shrimp gut, because denitrification cannot be fully established during the short gut passage time of food-associated bacteria. Nitrous oxide emission directly mediated by L. vannamei contributes significantly to the overall N(2)O emission from aquaculture facilities.